2020
DOI: 10.3390/ijerph17155473
|View full text |Cite
|
Sign up to set email alerts
|

Large for Gestational Age and Risk for Academic Delays and Learning Disabilities: Assessing Modification by Maternal Obesity and Diabetes

Abstract: The objective of this study was to examine academic delays for children born large for gestational age (LGA) and assess effect modification by maternal obesity and diabetes and then to characterize risks for LGA for those with a mediating condition. Cohort data were obtained from the New York City Longitudinal Study of Early Development, linking birth and educational records (n = 125,542). Logistic regression was used to compare children born LGA (>90th percentile) to those born appropriate weight (5–89th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Our findings are congruent with earlier reports [ 13 , 28 , 39 ] that state that influences of other gestational comorbidities and environmental factors are closely related to a child’s development. Among all intrauterine factors, gestational comorbidities such as hypertension [ 13 ] and obesity [ 13 , 16 , 17 , 35 ] also affect child development and, therefore, among children of diabetic mothers, those with other gestational comorbidities were more likely to be at risk developmentally.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are congruent with earlier reports [ 13 , 28 , 39 ] that state that influences of other gestational comorbidities and environmental factors are closely related to a child’s development. Among all intrauterine factors, gestational comorbidities such as hypertension [ 13 ] and obesity [ 13 , 16 , 17 , 35 ] also affect child development and, therefore, among children of diabetic mothers, those with other gestational comorbidities were more likely to be at risk developmentally.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, the risk for subnormal intellectual performance was dependent on a BMI at young adulthood BMI >30 OR 1.86 (1.58–2.19) ( 119 ). In the recently published study from the USA, a slightly decreased risk of poor academic performance was noticed for LGA children ( 122 ). In addition, one study from UK Biobank, the middle birth weight category showed better performance for hearing, vision, reaction time, and IQ than the highest category ( 123 ).…”
Section: Resultsmentioning
confidence: 93%
“…Eight cohort studies investigated the association between high birth weight and intellectual performance, seven with moderate and one with serious risk of bias. Five of these studies consisted of a study population of Nordic conscripts (117)(118)(119)(120)(121), one was a large cohort study of children born in Western Australia (104) and one study was from the USA (122). In five studies, no clear association was found between high birth weight and intellectual performance, risk of intellectual disability, or low IQ score (104,(117)(118)(119)121).…”
Section: Intellectual Performancementioning
confidence: 99%
“…Zu diesem Ergebnis kam auch eine Berliner Studie [11]. Duffany et al [41], denen zur Stratifizierung in Risikokollektive ein maternaler Gestationsdiabetes zur Verfügung stand, konnten hingegen zeigen, dass LGA-geborene Kinder von Müttern mit Gestationsdiabetes ein höheres Risiko für sonderpädagogischen Förderbedarf aufwiesen. Bei LGA-geborenen Kindern von Müttern ohne Gestationsdiabetes war dies nicht der Fall.…”
Section: Diskussionunclassified